2021
DOI: 10.1101/2021.09.01.458291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrovirus-induced leukemia – hijack of T-cell activation mechanisms revealed by single-cell analysis

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) mainly infects CD4+ T-cells and induces chronic, persistent infection in infected individuals with some progressing to develop adult T-cell leukemia/lymphoma (ATL). Whilst HTLV-1 alters cellular differentiation, activation and survival, it is unknown whether and how these changes contribute to malignant transformation of infected T-cells. In this study, we used single-cell RNA-Seq and TCR-Seq to investigate T-cell differentiation and HTLV-1-mediated transformation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that TRAF3IP3 plays a vital role in IFN-mediated antiviral innate immunity and participates in RIG-I-MAVS-mediated antiviral signaling (22). However, it is unclear which signaling pathway is activated by TRAF3IP3 in glioma and whether other crosstalk pathways are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that TRAF3IP3 plays a vital role in IFN-mediated antiviral innate immunity and participates in RIG-I-MAVS-mediated antiviral signaling (22). However, it is unclear which signaling pathway is activated by TRAF3IP3 in glioma and whether other crosstalk pathways are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-mediated proteolysis is reportedly associated with pancreatic cancer metastasis (21). Human T cell leukemia virus type 1 (HTLV-1) mainly infects CD4 + T cells and induces chronic, persistent infection in infected individuals, with some developing adult T cell leukemia/lymphoma (ATL) (22). Glioblastoma is one of the most aggressive and frequent primary brain tumors.…”
Section: Gsea Of Traf3ip3-related Degsmentioning
confidence: 99%
“…As both TCR-a and TCR-b sequences are typically expressed in conjunction and necessarily must interact with CD3 for the differentiation and survival of T cells, these skewed TCR clones may coincide with previous findings of reduced CD3 protein expression in ATL (81). A recent advance of TCR repertoire analysis with multiple bioinformatics analysis at single cell level also demonstrated that HTLV-1-infected cells in an activated state further transformed into ATL cells, which are characterized as clonally expanded, highly activated T cells (78). In addition, while healthy individuals harbored T cells with an activated phenotype, in ATL, infected T cells and ATL cells became spontaneously activated, acquired a regulatory T cell phenotype, and subsequently progressed to a state of extreme activation, which was maintained throughout the ATL phase (78).…”
Section: Tcr Repertoire Analysis In Atl Malignant T Cellsmentioning
confidence: 99%
“…A recent advance of TCR repertoire analysis with multiple bioinformatics analysis at single cell level also demonstrated that HTLV-1-infected cells in an activated state further transformed into ATL cells, which are characterized as clonally expanded, highly activated T cells (78). In addition, while healthy individuals harbored T cells with an activated phenotype, in ATL, infected T cells and ATL cells became spontaneously activated, acquired a regulatory T cell phenotype, and subsequently progressed to a state of extreme activation, which was maintained throughout the ATL phase (78). Thus, new technologies and bioinformatics tools at single cell level will further improve our ability to identify mechanistic pathways responsible for the in vivo transformation of HTLV-1infected T cells into leukemic cells.…”
Section: Tcr Repertoire Analysis In Atl Malignant T Cellsmentioning
confidence: 99%